The gifts of Athena : historical origins of the knowledge economy - Mokyr, Joel (Princeton University Press, 2005)
The growth of technological and scientific knowledge in the past two centuries has been the overriding dynamic element in the economic and social history of the world. Its result is now often called the knowledge economy. But what are the historical origins of this revolution and what have been its mechanisms? In The Gifts of Athena, Joel Mokyr constructs an original framework to analyze the concept of "useful" knowledge. He argues that the growth explosion in the modern West in the past two centuries was driven not just by the appearance of new technological ideas but also by the improved ac.